Money market fund reform: Dealing with the fundamental problem - Huberto M. Ennis; Jeffrey Malcolm Lacker; John A. Weinberg (Journal of Risk and Financial Management, 2023)
After the events in March 2020, it became clear to U.S. policymakers that the 2014 reform of the money market funds (MMFs) industry had not successfully addressed the stability concerns associated with surges in withdrawals. In December 2021, the SEC proposed a new set of rules governing how money market funds can operate. A fundamental problem behind the instability of money market funds is the expectation that backstop liquidity support will be provided by the government in the event of financial distress, along with the government's inability to credibly commit to not provide such support. This expectation dampens funds' incentives to take steps ahead of time to mitigate the risk of sudden withdrawals. The newly proposed reforms are aimed at constraining withdrawals or penalizing them with "swing pricing". We argue that if the commitment problem is the fundamental issue, it would be more useful to reduce expectations of ex-post support by requiring MMFs to have contractual commitments in place, ex-ante, for liquidity support from private parties.
Keywords: 650; regulation; financial stability; financial markets